Revolutionaries [videorecording] - Dormer, Mike; Fairley, John; Hughes, Gruyneth; Marshall, Jill; Welfare, Simon (Red Empire presented by Robert Conquest ; series producer, Gruyneth Hughes, 1990)
Covers massive empire rule of Nicholas and Alexandria ; ignition of workers movement during the Siberian gold fields strike of 1912; Tsar Nicholas commanding the army and the start of revolution. Describes the Siberian goldfields strike in 1912 which ignites the worker's movement.